Evaluation of the quality of university public transportation services in a city in Ceará using the Servqual tool - Lima, Paulo Ricardo Fernandes de; Ramalho, Lorena Alves; Santos, Ithalo Ricardo Damasceno dos; Oliveira, Talita Paloma de; Lima Júnior, George Soares (Brazilian Journal of Production Engineering, 2025)
Quality of university public transport is a determining factor in ensuring access to education, especially in inland cities, where the offer of mobility options is limited. Therefore, this work aimed to evaluate the quality of the university public transport service in a city in the interior of Ceará using the SERVQUAL tool. A version of the tool was built and adapted for the analyzed service. A representative sample was collected and questionnaires were administered to a group of service users. Subsequently, quality gaps were calculated, differences between perceptions and expectations regarding service quality, in five dimensions analyzed: tangibility, reliability, responsiveness, security and empathy. The results showed that, in general, the quality of the service provided presents a high degree of dissatisfaction among users in all dimensions analyzed, with emphasis on the responsiveness (gap = -1.86) and tangibility (gap = -1.21) dimensions, which presented the worst results. Finally, a mitigating action plan was presented for the reality encountered.